PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI NUSA RAYA CIPTA KECAMATAN SEMENDAWI SUKU III KABUPATEN OKU TIMUR - Rahmawati, Mustafiqoh; Ruliyansa, Ruliyansa (Jurnal Trisna Riset, 2024)
Savings and loan cooperatives are cooperatives whose members consist of several people who have a direct interest in the credit sector. This cooperative is very easy to find in Indonesian society. Usually, these cooperatives run special businesses in the credit sector which encourage their members and the community to save funds regularly. Apart from that, it also provides loans to each member for useful purposes by collecting fees (administration fees and interest, etc.) as low as possible. This research aims to determine the effect of work discipline on employee performance at the Nusa Raya Cipta Cooperative, Semendawai Suku III District, East OKU Regency. The hypothesis in this research is that there is a very strong influence between work discipline on employee performance at the Nusa Raya Cipta Cooperative, Semendawai Suku III District, East OKU Regency. Data collection techniques were carried out using field studies including observation, interviews, documentation and questionnaires. The analysis used in solving this research uses validity, reliability, simple linear regression and correlation coefficient tests. The research results show that work discipline has a very strong influence on employee performance with a correlation value of r = 0.96. Hypothesis testing also confirmed the significant relationship between the two variables. Therefore, companies are advised to improve work discipline to motivate employees and improve the quality of their work.